Gender Errors in French Interlanguage: The Effect of Initial Consonant Versus Initial Vowel of the Head Noun - Dewaele, Jean-Marc (Arborescences, 2015)
Many studies on gender assignment in French have focused on the effect of the final morpheme of the noun on the identification of the gender of the noun and the subsequent agreement with any determiners. The present study considers the effect of a noun’s initial vowel on gender accuracy in conversations with 36 Dutch-speaking French foreign language learners. The analysis of 1540 indefinite article + noun sequences revealed that gender accuracy was significantly lower when the noun started with a vowel. This effect was significant for French L3 learners but weaker among more advanced French L2 learners. It thus seems that an initial vowel, and the resulting gender syncretism, delays the correct identification of a noun’s gender among French L2 learners.